PREPARATION OF TEACHERS FOR MODERN VOCATIONAL SCHOOL: POLICULTURAL ASPECT, NEW TASKS AND DIRECTIONS OF RESEARCH (Pedagogy of Higher and Secondary Education, 2004)
The article deals with general problems the mankind is facing in the 21st, century and investigates the role of CISteachers, teachers from the Central and Western Europe in their decision. The author conducts a retrospective analysis of papers of inter national organizations (the UNO, UNESKO, MOP) in terms of a teacher rs role in the process of modernizing education.